PROSPECTS FOR FURTHER DEVELOPMENT OF THE DEPARTMENT OF MAXILLOFACIAL SURGERY - Muydinova Barnokhon Askarovna (Scholar Express Journals, 2022)
Currently, research is being conducted on the topic: "Development of new surgical methods of treatment and rehabilitation of patients using distraction ontogenesis, bioactive osteoplastic materials of a new generation to eliminate defects, deformations of the facial skull based on computer and laser technologies." The development of methods of endorses implantation in bone reconstructive operations have continued.
Keywords: implantation of the implants; surgical treatment; bone structure